Towards a Universal Health Coverage in the Pandemic COVID-19: Study on the Low Participation of Health National (JKN) in the District Bulukumba - Andi Irpan Badawi; Nurhudaeni Rahmiani; Muhammad Nurcholis Setiawan; Ashar Prawitno (Journal Research of Social Science, Economics, and Management, 2022)
The implementation of the National Health Insurance (JKN) program is aimed at realizing the SDGs (Sustainable Development Goals), namely achieving UHC (Universal Health Coverage) commitments in Indonesia. However, until now there are still many residents, especially in Bulukumba Regency, who are not registered for JKN membership. In fact, JKN participation greatly helps the accessibility of health services and overcomes obstacles to medical expenses, especially for low-income people. Therefore, the purpose of this study is to identify the factors causing the low JKN membership and formulate efforts to increase JKN participation in Bulukumba Regency. This research method is a qualitative research with the determination of informants using purposive techniques. This research was conducted in Bulukumba Regency in June 2021. Data collection techniques were carried out through interviews, observations, documentation, and literature studies, then the data were analyzed using fishbone diagrams. The results showed that the factors causing the low JKN participation in Bulukumba Regency, namely low education level, the majority work as farmers, do not know the JKN registration process, do not understand the health insurance system, lack of socialization, the formation of a stigma regarding differences in health services between JKN participants and patients. general, apathetic family heads, the data bank in the Integrated Social Welfare Data (DTKS) has no updates, there is no synchronization of data for the poor, and there is a quota system for the JKN PBI APBD. Based on this, it can be concluded that the cause of the low JKN participation in Bulukumba Regency arises from problems from the community and the government. Therefore, it is necessary to update the data at DTKS regularly and provide education and socialization to the public regarding the health insurance system and JKN program, then form an Independent Institution to foster community enthusiasm to register as JKN participants.